Sabar: Sebuah Konsep Psikologi - Subandi, M.A. (Fakultas Psikologi UGM, 2011)
This research aims at developing psychological concept of ‘sabar’ (patient) or ‘kesabaran’ (patience). These terms have become everyday life issues among Indonesian. However, most of the concept of patience derives from religious and cultural resources, none of them from psychological literature. Following a grounded theory method, there were two phases in this research. The first phase aiming at developing the concept of ‘sabar’ or ‘kesabaran’ derived from existing religious literatures in many different religious traditions. The second phase aiming at developing the concept of ‘sabar’ and ‘kesabaran’ based on empirical data. Ninety nine students of Master Profession of psychology participated in this research by responding to five open ended questions. The results of data analysis in phase one and phase two were compared. This research concluded that there were five aspects of ‘sabar’ (patient) or ‘kesabaran’ (patience): (1) self control (2) resilience (3) persistence (4) accepting reality, and (5) staying calm